The Correlation between Dehydration and Early Neurological Deterioration in Acute Hemorrhagic Stroke - Purba, Siti Hasnita Oktavia; Nasution, Iskandar; Pujiastuti, R.A. Dwi (CoinReads Media Prima, 2024)
Introduction: Early Neurological Deterioration (END) is a worsening of symptoms within a few hours or days after an acute stroke which occurs in around 25,5% of patients with intracerebral hemorrhage. Dehydration is one of the conditions that is widely observed as a non-neurological cause of END in acute ischemic stroke, but in hemorrhagic stroke the correlation is still unclear. The aim of this study was to determine the correlation between dehydration and END in acute hemorrhagic stroke. Method: In this cross-sectional study, we assessed acute hemorrhagic stroke patients within 72 hours of onset at Haji Adam Malik General Hospital Medan, Indonesia, from April to October 2023. Patients are categorized as dehydrated if BUN/Cr ≥15 and urine specific gravity >1,010. END was defined as an increase in National Institutes of Health Stroke Scale (NIHSS) score of ≥ 2 points on the total score, or ≥ 1 point on motor items. Bivariate analysis was carried out to determine the correlation between dehydration and END in acute hemorrhagic stroke using the contingency correlation test. Results: A total of 30 subjects were included, with a mean age of 56,47 ± 12,75 years and 53,3% women. In this study, END was identified in 11 (36,7%) patients and dehydration was detected in 13 (43,3%) patients. The results of statistical analysis found no significant correlation between dehydration and END in acute hemorrhagic stroke (p=0,88 and r=0,298). Conclusion: There was no significant correlation between dehydration and END in acute hemorrhagic stroke.